Pembelajaran Daring di Sekolah Dasar Pada Era Pandemi Covid 19 - Muhammad Iqbal Al Ghozali; Sri Fatmawati; Sofyan Mustoip (Jurnal IAI Bunga Bangsa Cirebon, 2021)
The Covid-19 pandemic has affected all sectors of human activity, including the education sector. The pandemic forced learning activities to be carried out online (online). Of course this is a new habit especially at the elementary school level where the learning process is carried out face-to-face in full. In overcoming these problems, various distance learning media in the form of applications were introduced to students and parents. However, there is an application that is familiarly used by students and parents of students that can be used for the online learning process, namely the Whatsapp application. The purpose of this study is to look at the online learning process in elementary schools during the Covid-19 pandemic era. This study uses a qualitative approach with survey research methods. The research subjects were teachers of SDN 1 Kalipasung in Cirebon Regency as well as research informants. The data collection technique was carried out by conducting in-depth interviews related to the process of implementing online learning for elementary school teachers during the Covid-19 pandemic. The activity of analyzing and presenting research data is carried out descriptively. The results of this study are Online Learning in Elementary Schools During the Covid 19 Pandemic Era, especially at SDN Kalipasung 1 when viewed from the learning process, it is only used as a means of sending assignments, but the learning process does not involve WhatsApp media completely. In the aspect of supervision, the teacher is also not fully able to monitor the student learning process, as a result, the teacher must cooperate with parents in conducting supervision. The responses of parents and students related to the online learning process stated that they wanted to return to carrying out normal learning (face to face) as usual because they felt they were not used to online learning. Abstrak Pendemi Covid-19 telah mempengaruhi segala sektor aktifitas kegiatan manusia, termasuk sektor pendidikan. Pandemi tersebut memaksa kegiatan pembelajaran dilakukan secara dalam jaringan (daring). Tentu ini menjadi kebiasan baru apalagi di jenjang sekolah dasar yang mana proses pembelajaran dilakukan secara tatap muka secara penuh. Dalam mengatasi permasalah tersebut, berbagai media pembelajaran jarak jauh dalam bentuk aplikasi mulai diperkenalkan kepada siswa maupun orangtua siswa. Namun ada aplikasi yang familiar digunakan oleh siswa maupun orang tua siswa yang dapat digunakan untuk proses pembelajaran daring yakni aplikasi Whatsapp. Tujuan dari penelitian ini yakni untuk melihat proses pembelajaran daring di sekolah dasar pada era panedemi Covid – 19. Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian survei. Subjek penelitian ialah guru-guru SDN 1 Kalipasung yang ada di Kabupaten Cirebon sekaligus menjadi informan penelitian. Teknik pengumpulan data dilakukan dengan melakukan wawancara mendalam (In-depth Interview) terkait proses pelaksanaan pembelajaran daring guru Sekolah Dasar selama pandemik Covid-19. Kegiatan analisis dan penyajian data hasil penelitian dilakukan secara deskriptif. Hasil penelitian ini yakni Pembelajaran Daring di Sekolah Dasar Pada Era Pandemi Covid 19 khususnya di SDN Kalipasung 1 jika ditinjau dari proses pembelajarannya hanya dijadikan sebagai sarana pengiriman tugas, tetapi proses pembelajaran tidak melibatkan media whatsapp sepenuhnya. Dalam aspek pengawasan juga tidak sepenuhnya guru dapat memantau proses belajar siswa, alhasil guru harus bekerjasama dengan orang tua dalam melakukan pengawasan. Adapun respon orangtua siswa dan siswa terkait dengan proses pembelajaran daring menyatakan ingin kembali melaksanakan pembelajaran secara normal (tatap muka) seperti biasa karena merasa belum terbiasa dengan pembelajaran daring.